Early Macrophage Activation in Preterm Newborns and Respiratory Disease - Milan, Anna; Priante, Elena; Nardo, Daniel; Tosato, Francesca; Pantano, Giorgia; Baraldi, Eugenio; Zaramella, Patrizia (Journal of Child Science, 2017)
Monocyte-macrophages have a role in host defense and tissue remodeling. Classically activated (M1) and alternatively activated (M2) macrophages from preterm newborns are analyzed, and the role in acute respiratory distress syndrome (RDS) and bronchopulmonary dysplasia (BPD) is evaluated. Observational study was conducted on the blood samples (BSs) and tracheal aspirates (TAs) collected at 48 to 72 hours of life in preterm newborns. Flow-cytometry was performed to identify monocytes and M1 or M2. Prenatal factors, gestational age, birth weight, acute RDS and BPD were assessed and related to the M1 and M2 levels and M2/M1. One hundred nine subjects were included, and 100 were followed up. M1 and M2 increase and decrease, respectively, according to the gestational age and birth weight. Higher M2 and lower M1 levels in TAs were found after maternal chorioamnionitis. BPD patients have low M1 with high M2 in blood samples (BSs), as well as in tracheal aspirates (TAs). No relation was found between activation pattern and prenatal variables or the RDS grade. The correlation between gestational age or birth weight and M1 could reflect a more mature macrophage system, capable to push undifferentiated macrophages toward the classical pathway. We speculate that adequate early classical macrophage activation could be crucial to protect lungs from post-natal injuries, preventing the development of BPD.
Keywords: bronchopulmonary dysplasia; macrophage; preterm newborn; respiratory distress syndrome